2005
DOI: 10.1086/430820
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Halo Inside‐Out Growth for the X‐Ray Properties of Nearby Galaxy Systems within the Preheating Scenario

Abstract: We present an entirely analytic model for a preheated, polytropic intergalactic medium in hydrostatic equilibrium within a NFW dark halo potential in which the evolution of the halo structure between major merger events proceeds inside-out by accretion. This model is used to explain, within a standard ΛCDM cosmogony, the observed X-ray properties of nearby relaxed, non-cooling flow groups and clusters of galaxies. We find that our preferred solution to the equilibrium equations produces scaling relations in ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 95 publications
2
9
0
Order By: Relevance
“…This result holds for both adiabatic and radiative simulations (but see Kay et al 2004) and agrees well with the effective À derived from observed clusters by Finoguenov et al (2001). Solanes et al (2005) find that À ¼ 1:2 offers the best consistency with the assumption that the specific energy of the hot gas equals that of the dark matter. Interestingly, the purely adiabatic, spherical, and self-similar collapse solution of Bertschinger (1985) was also polytropic with À % 1:17.…”
Section: Polytropic Rearrangementsupporting
confidence: 85%
See 2 more Smart Citations
“…This result holds for both adiabatic and radiative simulations (but see Kay et al 2004) and agrees well with the effective À derived from observed clusters by Finoguenov et al (2001). Solanes et al (2005) find that À ¼ 1:2 offers the best consistency with the assumption that the specific energy of the hot gas equals that of the dark matter. Interestingly, the purely adiabatic, spherical, and self-similar collapse solution of Bertschinger (1985) was also polytropic with À % 1:17.…”
Section: Polytropic Rearrangementsupporting
confidence: 85%
“…Aside from the innermost region, the model with a À of 1.2-1.4 satisfactorily represents the T falloff in the outer regions, which contain most of the gas mass. À ¼ 1:2 1:4, corresponding to polytropes with index n ¼ 2:5 5, provides adequate fits to the outer parts of the clusters, within which resides most of the gaseous mass (see also the discussion in Solanes et al 2005). Ascasibar et al (2003) have shown that a À ¼ 1:18 model is a good fit to the average temperature profile measured by Markevitch et al (1998); this latter measurement has been confirmed by De Grandi & Molendi (2002), Piffaretti et al (2005), and Vikhlinin et al (2005).…”
Section: Resulting Profilesmentioning
confidence: 99%
See 1 more Smart Citation
“…AMIGA follows this growth in a well-contrasted analytic manner with no free parameters (Salvador-Solé et al 1998, 2007Raig et al 2001). This allows us to accurately calculate, at any given moment, their abundance (Juan et al 2014a(Juan et al , 2014b and inner structure and kinematics (Salvador-Solé et al 2012a, which in turn sets the structure and temperature of their hot gas (Solanes et al 2005). The amount and metallicity of such a hot gas and the properties of the central galaxy and its satellites are monitored in AMIGA from the individual halo aggregation history.…”
Section: Luminous Sourcesmentioning
confidence: 99%
“…This gives a rough estimation of the slope at the virial radius in the range 2.64 to 2.36, which is in satisfactory agreement with the models based on the results of N-body simulations as those described in the introduction. For ∆ vir , we use the model ∆ vir (a) = 178Ω 0.45 m (a) resulting in ∆ vir ≈ 100 at present epoch (a = 1) (see Solanes et al 2005).…”
Section: Resultsmentioning
confidence: 99%